Fulminant Familial Hemophagocytic Lymphohistiocytosis (FHL) in an infant masquerading septic shock - A case report - Rohit Kapoor; Prabhas Prasun Giri; Joydeep Das (Wolters Kluwer Medknow Publications, 2016)
Hemophagocytic lymphohistiocytosis (HLH) is a rare but life-threatening disease caused by uninhibited hyperinflammatory reaction that can lead to fulminant, life threatening multi organ failure and whose pathophysiology and clinical characteristics are somehow similar to that of severe sepsis and septic shock. Here we present a case of a 5 months old baby, admitted in our PICU in shock and was being managed initially in the lines of septic shock but ultimately was diagnosed to be a case of Familial HLH type 2 due to a homozygous missense variation in exon 2 of the PRF1 gene that results in the amino acid substitution of Serine for Tryptophan at codon 129.